Associations between circulating amino acids and metabolic dysfunction‐associated steatotic liver disease in individuals living with severe obesity - Ina Maltais‐Payette; Jérôme Bourgault; Marie‐Frédérique Gauthier; Laurent Biertho; Simon Marceau; François Julien; Patricia L. Mitchell; Christian Couture; Francis Brière; Jacques Corbeil; Benoit J. Arsenault; André Tchernof (Physiological Reports)
Abstract Metabolic dysfunction‐associated steatotic liver disease (MASLD) describes liver diseases caused by the accumulation of triglycerides in hepatocytes (steatosis) as well as the resulting inflammation and fibrosis. Previous studies have demonstrated that accumulation of fat in visceral adipose tissue compartments and the liver is associated with alterations in the circulating levels of some amino acids, notably glutamate. This study aimed to investigate the associations between circulating amino acids, particularly glutamate, and MASLD. In addition, we hypothesized that liver steatosis, concomitant with visceral adiposity, could contribute to the association between circulating glutamate and visceral obesity. We studied a sample of 150 patients living with severe obesity who were non‐diabetic and selected to represent a wide range of MASLD severity. Liver histological features were determined by a pathologist from a biopsy sample obtained at the time of bariatric surgery. Bulk RNA sequencing measured the hepatic mRNA expression level of selected genes related to the urea cycle and glutamate metabolism. Fasting plasma amino acid levels were measured by liquid chromatography coupled with tandem mass spectrometry. Patients with more advanced steatosis had larger visceral adipocytes, higher levels of circulating tyrosine, glutamate, and alanine as well as lower levels of serine. MASLD severity was significantly associated with the hepatic mRNA expression of glutamate metabolism genes such as GLS1, GLUL (positively), and NAGS (inversely). In individuals living with obesity, MASLD severity is associated with visceral adipocyte hypertrophy, higher circulating glutamate as well as potential alterations of hepatic amino acid and nitrogen metabolism.